Process Efficiency Analysis of Selected Automotive Companies in Europe - Kveta Papouskova; Martin Telecky; Jiri Cejka (Communications - Scientific letters of the University of Zilina, 2020)
The automotive industry has lately been undergoing major changes having a considerable impact on the whole vehicle sector. This does not only refer to what is technologically new on vehicles themselves, but also to the new modern management methods, frequently associated with the Industry 4.0 concept. As well as other companies, car factories are pushing their costs downwards to increase their production efficiency. This paper analyses the economic situation of 5 car manufacturers, two of which having their factories in the Czech Republic and three in Germany. The task was to ascertain efficiency of individual companies in order to propose possible improvements. To do this, the Data Envelopment Analysis (DEA) for two models (CCR - model based on Charnes, Cooper & Rhodes and BCC - model based on Banker, Charnes & Cooper) was used. The BCC model was found to be more applicable to the established efficiencies, than the CCR one.